FACTORS AFFECTING THE USE OF E-MONEY (STUDY ON E-MONEY USER IN CITY OF SOUTH TANGERANG) - Widiyati, Dian; Hasanah, Neneng (ACCOUNTABILITY, 2020)
The purpose of this study is to analyze the factors that influence the use of e-money. The type of study is a quantitative method questionnaires distributed in soft copy (Google Form). The samples included 107 people who lived in the city of South Tangerang, Banten. Samples are taken by simple random sampling technique. The analytical method used is the analysis of multiple data processing using E-Views 8. The results of this experiment show that the variables of Perceived Benefit and Compatibility does not affect the use of e-money, while Perceived Usefulness variables influence the use of e-money and also, Perceived of Benefit, Compatibility and Perceived Usefulness affect on the use of e-money together.